Oxyfluorides for electrochemical and photoelectrochemical water oxidation: a review and basic tutorial - Ryusuke Mizuochi; Kazuhiko Maeda (Journal of Asian Ceramic Societies)
The development of materials that not only exhibit high performance but are also cost-effective for (photo)electrochemical water oxidation is crucial for sustainable hydrogen production through water splitting. Oxyfluorides, a unique class of mixed-anion compounds containing fluoride and oxide ions in the same crystal-structure phase, have recently attracted attention for use in various applications because of their characteristic electronic properties derived from the presence of highly electronegative fluorine. This review provides a comprehensive summary of the advances in oxyfluoride electrocatalysts and photoanodes for water oxidation. We discuss the effects of fluorine in amorphous, mixed-phase, and single-phase oxyfluoride electrocatalysts, highlighting their role in improving water oxidation performance. We also explore the potential of oxyfluoride photoanodes for water oxidation, demonstrating their visible-light responsivity and intrinsic stability under operating conditions. We emphasize the interplay between fluorine complexation and water oxidation activities of the electrocatalysts and photoanodes and provide perspectives on future directions in the field of oxyfluoride-based water oxidation systems, including insights into the design of new oxyfluoride materials for water oxidation.